THE THEORETICAL MODEL OF PEDAGOGICAL ACTION RESEARCH IN THE CONFIGURATION OF THE CURRENT SIGNIFICANCE ASSIGNED TO ACTION RESEARCH - Diana ANTOCI; Maia BOROZAN (Analele Universităţii din Craiova. Psihologie, Pedagogie)
The article highlights the increasing focus on clarifying the concept of pedagogical action research (PAR) and its critical role in the professional development of educators. It emphasizes the importance of designing and conducting PAR to cultivate investigative competence and foster innovation within educational settings. By refining the theoretical framework of PAR, the article lays the groundwork for advancing contemporary pedagogical thinking, with an emphasis on integrating innovative practices into education to enhance efficiency and effectiveness. The Theoretical Model of Pedagogical Action Research, developed as part of this work, addresses the gaps in existing definitions and models by emphasizing the specificity of PAR. It outlines a framework for the cyclical development of competences such as conceptualizing research, strategic management, critical reflection, educational innovation, re-planning of pedagogical action research etc. This Model provides a structured approach to conducting PAR while advancing educators’ abilities to adapt to dynamic teaching environments. Additionally, the paper underscores the benefits of PAR for teachers, including improved problem-solving skills, renewed teaching strategies, and enhanced selfreflection. These qualities contribute to continuous professional growth and resilience in addressing challenges in teaching. Furthermore, PAR equips teachers to respond effectively to contemporary educational demands, such as integrating students with special needs, managing cultural diversity, and aligning with evolving labor market requirements. In the context of globalized education, PAR fosters educators’ preparedness to guide students in navigating an interconnected world. By integrating PAR practices, teachers not only enhance their professional competences but also strengthen their capacity to drive educational innovation, ensuring their relevance and impact in a rapidly changing educational landscape.